Development of lecturers' publication score algorithm / Zamali Tarmudi and Haijon Gunggut - Zamali Tarmudi; Haijon Gunggut (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
The aim of this paper is to develop a lecturers' publication score algorithm to assist UiTM Sabah in selecting winners among lecturers in terms of publication contribution. It focuses on how the evaluation committee identifies and determines the score for categories of different publication materials such as journal articles, proceedings, books, and chapter in a book, technical report, etcetera and the justification for the weightage given for each category. Apart from that, the technical aspects such as the type of indexes, role of authors and the level of publications are also discussed thoroughly by the committee until reaching a certain degree of consensus. Based on predetermined characteristics, a comprehensive algorithm was designed with multiple factor bases using the fuzzy evaluation approach. Then, an intial simulation testing was performed by using Microsoft Excel 2010 to simulate the datasets which were obtained from UiTM Sabah. This process is vital to determine the feasibility and suitablility of the proposed algorithm. The results showed that, the proposed algorithm is highly beneficial to the evaluation committee and can significantly reduce the time consumed in the evaluation process . Thus, it can facilitate the task of the committee to make decisions in an easier, transparent and systematic manner.